Non prioritized answer set revision - Simari, Gerardo I. (2004)
In this paper, we build on previous work on Belief Revision operators based on the use of logic programming with Answer Set semantics as a representation language. We present a set of postulates for Answer Set Revision with respect to a set of sentences and with respect to explanations. We focus on the non-prioritized revision operator with respect to explanations, or arguments, which is intended to model situations in which agents revise their knowledge as a result of dialogues with other agents in a multi-agent setting.